ANALISIS TINGKAT KEPUASAN KONSUMEN ROTI GANDA DI TOKO GANDA KOTA PEMATANGSIANTAR - Maria Margareth Simarmata; Basuki Sigit Priyono; Ridha Rizki Novanda (Jurnal Agroindustri, 2023)
Roti Ganda is a typical bread from Pematangsiantar, white bread made from flour, sugar, eggs, margarine, and other ingredients. Toko Ganda is shops that have long been established and still exists. So the researcher wants to know the opinions of consumers regarding the attributes of Toko Ganda that need to be improved again so that it becomes a store that still exists. This study aims to analyze Roti Ganda's customer satisfaction at Toko Ganda and analyze the attributes of Roti Ganda that need to be improved. The respondents used in the study were based on the results of Slovin's calculations of 96 people. The data collection method was carried out using the accidental sampling method. The location of this research was carried out purposively in Pematangsiantar City. The research method used is the Customer Satisfaction Index (CSI) Method and the Potential Gain in Customer Values (PGCV) Method. The results showed that the CSI value in this study was 82.60%, which was included in the very satisfied category. The PGCV index value shows attributes that need to be improved again, namely the parking location. The results showed that the CSI value in this study was 82.60%, included in the category of very satisfied. In contrast, the attributes of Toko Ganda that need to be increased are found in the location attributes, namely parking lots. The need for parking space is getting more significant because the volume of traffic that leaves or goes to the activity center increases. Parking space that cannot meet the needs results in roadside around the area; thus, expected more parking spaces.